Cytotoxic, Antioxidant, and Caspase-9 activity of 2-(3,5-dibromo-4-methoxyphenyl)3(3-mercapto-5(pyridine-4-Yl)4H1,2,4-triazol-4yl)-thiazolidine4-one against various human tumor cell lines - Hassan, Firas A (Al-Nahrain Journal of Science, 2018)
Caspase, or cysteine-dependent aspartate-directed proteases, belong to a extremely protected group of cysteine proteases that have a crucial role within the numerous phases of apoptosis. The derivative of 2-(3,5-dibromo-4-methoxyphenyl)-3(3-mercapto-5(pyridine-4-yl)-4H1,2,4-triazol-4-yl)-thiazolidine4-one (C3) described a high toxic efficacy in murine melanoma tumor(B16F10), human prostate tumor (LCCaP), and non-small cell lung tumor (H1299) by measured half maximal inhibitory concentration IC50 values were 41 µg/ml, 54.11 µg/ml , and 109.9 µg/ml , respectively, which was the most significant cytotoxic towards (B16F10) cell line treated at (P